UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA MELALUI TUTOR TEMAN SEBAYA BAGI SISWA KELAS IX SMP NEGERI 3 TASIKMADU PADA SEMESTER II TAHUN PELAJARAN 2014/2015 - Surono Surono (JURNAL MITRA SWARA GANESHA, 2015)
AbstractClassrooms action research aims to improve the learning achievements of students through peers tutoring for the students of class IX Secondary Schools Tasikmadu Negeri 3 Semester II in 2014-2015. This research desaigns with class action model spiral of Kemmis and Taggart (1988). Source data obtained from the informants, a source of events and documents the results of the study. Class action research is conducted collaboratively. Research procedures include preparation, initial description, planning, action, observation, evaluation and reflection.Data collection techniques used observation, interviews, tests, documentation and question form. Technique of data analysis using the techniques of critical analysis and comparative analysis. Based on the results of the learning achievements of students prior to the cycle I have elevated the 53 % with 4 students graduating student learning outcomes, KKM cycle I to II cycle 14 % has increased by 26 students or all students graduating KKM.Test results show that the effectiveness of peer tutors are effective methods of improving student learning achievement good students as members of the Group t test (paired t test) of thit 43.19 where probability sig. 0.00 < 0.05 and students as tutors or the leadership of the Group t test (paired t test) of thit 6.459 where probability sig. 0.00 < 0.05. The conclusions of this research that peer tutors effectively enhance the learning achievements of students of class IX SMP Negeri 3 Tasikmadu II year Semester lesson 2014-2015. Keywords: Peers tutoring, learning outcomes